Long term surgical outcomes of unilateral recession-resection versus bilateral lateral rectus recession in basic-type intermittent exotropia in children - Dong Hyun Kim (Nature Portfolio, 2021)
Abstract The long-term results of surgical treatment of intermittent exotropia (X(T)) according to the type of surgery are controversial. We conducted a retrospective cohort study to compare the long-term results between unilateral recession-resection (RR) and bilateral lateral rectus recession (BLR) with an average follow-up of 9.5 years in children with basic-type X(T). Patients with basic-type X(T), who underwent RR (RR group) or BLR (BLR group) and were followed-up for more than 5 years postoperatively, were analyzed. Of the 560 patients, 363 patients received BLR and 197 patients underwent RR. There was no significant difference in the success rates between the two groups until postoperative 3 years. At an average of 9.5 ± 2.6 years after surgery, the success rate of the RR group was significantly higher than that of the BLR group starting from the fourth post-operative year until the last follow-up examination (64.5% vs 43.3%, P < 0.001). By multivariate analysis, preoperative hyperopia of more than + 2.00 diopters, younger age of onset, younger age at surgery, larger exodeviation at near than at distance of > 5 prism diopters, and the type of surgery (BLR) were risk factors of recurrence. In conclusion, RR was more successful than BLR with a lower recurrence rate in the long-term follow-up of patients with basic-type X(T).